Consciência, afetividade e política: a psicologia histórico-cultural na era da desinformação - Petrola, Domingos Arthur Feitosa (2021)
Theoretical transformations also accompany the social transformations and the ways of sociability that society has built. It is an era of full information exchange, where concepts and theories are quickly updated through quick access to new data. The data-centric model of society suggests that the production of science is always based on verifiable facts and it should understand reality according to the current demands of people. However, the speed of exchanges and the control of life by those who hold power through information often makes some data received deviate from the concrete reality shared that becomes curtained. For this reason, some authors have argued that we would be in an Age of Disinformation. Hence the need for constant reflection and review of theories and information is required. Historical-Cultural Psychology (PHC) is a theory that had its beginnings after the Russian Revolution of 1917 and its theoretical-methodological framework reflected the ideas that arose and ebbed in Soviet psychology at that time. From the end of the '80s and the beginning of the '90s, these constructions were taken to other parts of the globe and Vygotsky would become known worldwide in this period. Since then, publications around the PHC have increased significantly, having as reference the initial works, but also some recent discoveries. Given the above, this work was divided into two parts: a theoretical review and an analysis of concepts, and a reflection in the form of a theoretical essay on the historical-cultural praxis in this society of disinformation. For this reason, it became important to understand how Historical-Cultural Psychology, based on revisionist studies, could contribute to the analysis of some key concepts listed based on the understanding of human development, namely, consciousness, affectivity and politics in this Era of Disinformation. As a methodological process, a lexical analysis was carried out, therefore of a qualitative and bibliographic character, using the IRAMUTEQ software. Applying inclusion and exclusion criteria based on the year of publication, original language, the articles were submitted to an Analysis of Similarity and Descending Hierarchical Classification (CHD). Concerning the concept of consciousness, it was found that most articles still misuse the Activity theory to explain the development of senses by the subject, understanding development as an act of interiorization of activity. In this way, the resumption of the concept of perezhivanie, as a dramatic experience, and the idea of ​​a social situation of development is essential. About the concept of affectivity, there is confusion between emotions as a historical construction in the human psyche, therefore part of development, and emotions as an affective element in the educational activities, as some articles point to affectivity as a facilitating strategy in education, and not as part of the dialectical synthesis of the subjects' experience. Finally, around the concept of policy, the articles dealt with the application of theory in the field of institutional policy and public policies, where it is observed that the understanding of the development of higher psychological functions is the understanding of political subjects in their process of becoming a human being in institutional and public relations. Thus, the main point of this analysis indicates that human development is a political development; where consciousness and affections as psychological categories allow not only the understanding of hominization, but also become points of analysis of social reality, and which end up pointing to the outline of a historical-cultural praxis where it is necessary to recognize revolution as part of human development.